A high-strength pure cellulose hydrogel and preparation method thereof

By using natural hemp plant fibers to prepare high-strength pure cellulose hydrogels, and using a three-dimensional cross-linking network structure of micron-scale hemp fibers and regenerated nanofibers, the problem of insufficient strength and toughness of existing hydrogel materials is solved, and a high-strength, high flexibility and green and environmentally friendly hydrogel materials are achieved.

CN115819799BActive Publication Date: 2025-04-08NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211470619.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2025-04-08
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

The existing hydrogel materials have problems such as low gel strength, poor toughness and slow water absorption speed, making it difficult to prepare high-strength and high-flexibility hydrogels without adding other substances.

Method used

High-strength pure cellulose hydrogels are prepared using natural hemp plant fibers. Through the longitudinal arrangement of micron-scale hemp fibers and the three-dimensional cross-linking network structure of regenerated nanofibers, a dense skeleton is formed to improve the mechanical properties of the hydrogel.

Benefits of technology

It has achieved high strength and flexibility hydrogel materials, with excellent tensile strength and tensile strain, and is cheap and simple in technology. It is suitable for large-scale industrial production, and is completely biodegradable and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003958387490000011
    Figure HDA0003958387490000011
  • Figure HDA0003958387490000012
    Figure HDA0003958387490000012
  • Figure HDA0003958387490000021
    Figure HDA0003958387490000021
Patent Text Reader

Abstract

The present invention discloses a high-strength pure cellulose hydrogel and a preparation method thereof. The hydrogel is prepared from natural hemp plant fibers, wherein the micron-sized hemp fibers are arranged longitudinally to form a reinforcing skeleton, and the regenerated nanofibers obtained by partially dissolving the hemp plants are dispersed around the micron-sized hemp fibers to form a three-dimensional cross-linked network structure, which is translucent in appearance and has high tensile strength. The preparation method of the present invention is as follows: first, the lignin and hemicellulose of the natural hemp fibers are partially removed by chemical methods; then swelling and partial dissolution treatment are performed; finally, after standing treatment, the chemical solution is replaced with water to obtain a high-strength pure cellulose hydrogel. The hydrogel prepared by the present invention has high tensile strength, good chemical stability, and has abundant raw material sources, low cost, and simple preparation process, without the need to add any other substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength pure cellulose hydrogel and a preparation method thereof, and belongs to the technical field of hydrogel material preparation. Background Art

[0002] Hydrogel is a highly hydrated polymer network, similar to the "soft and wet" properties of human soft tissue, and is increasingly valued. However, hydrogels currently usually have disadvantages such as low gel strength, poor toughness and slow water absorption, which greatly limits the application of hydrogels. Therefore, a large number of studies are devoted to improving the mechanical properties of hydrogels, including double network hydrogels, physical or chemical cross-linked hydrogels and interpenetrating scaffold hydrogels. Recently, inspired by biological soft tissues with ordered nanocomposite structures, researchers have introduced highly ordered or aligned skeletons into hydrogels and expect to further improve their mechanical properties. Although five major artificial methods have been proposed, including magnetic field-oriented alignment, electric field-oriented alignment, strain-oriented alignment, oriented freezing and self-assembly, to obtain the oriented structure of hydrogels, it is still challenging to achieve oriented skeletons using the natural structure of sustainable biological resources.

[0003] In recent years, cellulose nanofibers extracted from wood have been widely used as reinforcing agents for the preparation of strong hydrogels due to their excellent mechanical properties. However, the preparation process of these nanocomposites usually involves multiple steps, including nanofibrillation of cellulose using chemical, mechanical or biological methods, and reconstruction through bottom-up approaches. Although bottom-up approaches can provide fine control of material structure, the steps are cumbersome and the manufacturing process cost is relatively high, and the manufacturing yield and efficiency are low.

[0004] Another method is to delignify the wood cell walls, retaining the original overall cell morphology and neatly arranged crystalline cellulose fiber skeleton, while greatly increasing the porosity of the cell walls. The weak and tough polyacrylamide (PAM) hydrogel is then combined with the strong and hard delignified cellulose fiber skeleton to obtain a strong and hard anisotropic wood hydrogel. However, crystalline cellulose is very hard and it is difficult to provide the hydrogel with ultra-flexible and highly elastic properties. There has always been great difficulty in preparing a green and environmentally friendly high-strength, high-flexibility hydrogel composed entirely of natural fibers without adding other substances. Summary of the invention

[0005] In view of the above-mentioned deficiencies and defects of the prior art, the object of the present invention is to provide a high-strength pure cellulose hydrogel and a preparation method thereof which is low-cost, simple in process and does not require the addition of other ingredients.

[0006] The technical solution adopted by the present invention is:

[0007] A high-strength pure cellulose hydrogel is prepared from natural hemp plant fibers, wherein the micron-sized hemp fibers are arranged longitudinally to form a reinforcing skeleton, and regenerated nanofibers obtained by partially dissolving the hemp plant are dispersed around the micron-sized hemp fibers to form a three-dimensional cross-linked network structure.

[0008] Furthermore, the diameter of the micron-sized hemp fiber is 15-50 μm, and the diameter of the regenerated nanofiber is 5-60 nm.

[0009] Furthermore, the water content of the hydrogel is 80-93%, the longitudinal tensile strength is in the range of 1.8-2.6 MPa, and the tensile strain is 50-69%.

[0010] The present invention also provides a method for preparing a high-strength pure cellulose hydrogel, comprising the following steps:

[0011] (1) placing the hemp plant in a mixed aqueous solution of sodium hydroxide and sodium sulfite in a water bath for heating to partially remove lignin and hemicellulose; and then washing with clean water to remove residual chemicals;

[0012] (2) placing the hemp fiber obtained in step (1) in a hydrogen peroxide water bath for heating to further remove lignin; then washing with clean water and freeze-drying;

[0013] (3) placing the dried hemp fibers in a mixed solution of N,N-dimethylacetamide and lithium chloride for heating so that the hemp fibers swell, and then allowing the swollen hemp fibers and the mixed solution to stand at a certain temperature;

[0014] (4) The material after static treatment is replaced with clean water to obtain a high-strength pure cellulose hydrogel.

[0015] Furthermore, in step (1), the water bath heating temperature is 100° C., and the treatment time is 5-15 hours.

[0016] Furthermore, in step (2), the concentration of the hydrogen peroxide solution is 5-30 wt.%, the water bath temperature is 100° C., and the heating time is 1-6 hours.

[0017] Furthermore, in step (3), the mass ratio of the mixed solution of N,N-dimethylacetamide and lithium chloride is in the range of 9:1 to 13:1, the heating treatment temperature is 100° C., and the heating treatment time is 0.5-2 hours.

[0018] Furthermore, in step (3), the mass ratio of the swollen hemp fiber to the mixed solution is in the range of 1:8 to 1:15, the standing time is 12-72 hours, and the standing temperature is 70-80°C.

[0019] Compared with the prior art, the advantages of the present invention are:

[0020] (1) Pure cellulose hydrogel has a three-dimensional cross-linked network structure and has excellent tensile strength of up to 2.6 MPa, which is superior to most existing hydrogel materials.

[0021] (2) The raw materials are natural hemp plant fibers, which are widely available, such as common ramie, flax and other fibers, and are low in cost.

[0022] (3) The preparation process is simple, the instruments and equipment are simple, the production cost is low, and it can be applied to large-scale industrial production.

[0023] (4) The hydrogel of the present invention is composed only of cellulose fibers, does not contain any additives, is completely biodegradable, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a real picture of the high-strength pure cellulose hydrogel of the present invention, which is translucent in appearance.

[0025] Figure 2 This is a scanning electron microscope cross-sectional morphology of the high-strength pure cellulose hydrogel prepared in Example 1.

[0026] Figure 3 This is an electron microscope image of the interlaced entangled structure of high-strength pure cellulose hydrogel micron fibers prepared in Example 1.

[0027] Figure 4 This is an electron microscope image of the surface regenerated fiber of high-strength pure cellulose hydrogel prepared in Example 1.

[0028] Figure 5 This is the stress-strain curve of the high-strength pure cellulose hydrogel prepared in Example 1. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.

[0030] The present invention provides a high-strength pure cellulose hydrogel, which is reconstructed from fibers extracted from natural hemp plants such as ramie, jute or flax. The hydrogel is composed of micron fibers with a diameter of 15-50 μm and dissolved and regenerated nanofibers with a diameter of 5-60 nm. Ramie micron fibers are arranged longitudinally to form a reinforcing skeleton with a certain orientation, and some dissolved and regenerated nanofibers are intertwined and entangled with each other and dispersed around the micron fibers to form a dense three-dimensional cross-linked network structure. Figure 1As shown. The pure cellulose hydrogel prepared by the present invention does not contain any other additives, and is only bonded by crosslinking, entanglement and hydrogen bonding between fibers, and maintains ultra-high longitudinal tensile strength. The high-strength pure cellulose hydrogel prepared by the present invention is completely biodegradable, environmentally friendly, has both superior performance and broad application scenarios, and has good commercial prospects.

[0031] The present invention also provides a method for preparing the above-mentioned high-strength pure cellulose hydrogel, comprising the following steps:

[0032] (1) The hemp plant is placed in a mixed aqueous solution of sodium hydroxide and sodium sulfite and heated in a water bath to partially remove lignin and hemicellulose; then the hemp plant is washed with clean water to remove residual chemicals.

[0033] (2) The hemp fiber from which lignin has been partially removed obtained in step (1) is placed in a hydrogen peroxide water bath and heated for a period of time to further remove the lignin; the fiber is then washed with clean water and freeze-dried.

[0034] (3) The delignified flax fiber obtained in step (2) is placed in a mixed solution of N,N-dimethylacetamide and lithium chloride for heating for a period of time, and then the flax fiber and the mixed solution are kept warm at 70° C. in a certain ratio.

[0035] (4) placing the sample obtained in step (3) in clean water, and replacing the chemical residues with water to obtain a high-strength pure cellulose hydrogel.

[0036] Example 1

[0037] The ramie was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 10 hours to partially remove lignin and hemicellulose; then washed with clean water. The partially lignin-removed ramie fiber was then placed in a 30wt.% hydrogen peroxide water bath at 100°C for 2 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified ramie fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 10:1 and heated at 100°C for 2 hours, and then the swollen ramie fiber and the above mixed solution were placed at 70°C for 48 hours in a mass ratio of 1:10. Finally, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 89%. Figure 2 This is a scanning electron microscope cross-sectional morphology of the high-strength pure cellulose hydrogel prepared in this example, showing the three-dimensional cross-linked structure inside the hydrogel. Figure 3This is an electron microscope image of the intertwined entangled structure of the above-mentioned high-strength pure cellulose hydrogel micron fibers. From the image, it can be seen that there are still some undissolved micron fibers with a size of about 20-30μm tightly interwoven inside the hydrogel, which serve as the skeleton of the hydrogel and provide the hydrogel with excellent mechanical tensile properties. Figure 4 This is an electron micrograph of regenerated cellulose on the surface of the hydrogel. It can be seen from the figure that there are a large number of dissolved and regenerated mesh-structured fibers with a size of 10-50nm on the surface. Figure 5 This is the stress-strain curve of high-strength pure cellulose hydrogel. During measurement, the hydrogel is first cut into uniform thin sheets, then cut into dumbbell shapes in an appropriate mold, and then placed between the two clamps of a mechanical tensile testing machine for stretching. The tensile strength is 2.6 MPa and the tensile strain is 63.5%, showing excellent mechanical properties.

[0038] Example 2

[0039] The flax was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 12 hours to partially remove lignin and hemicellulose; then washed with clean water. The partially lignin-removed flax fiber was then placed in a 30wt.% hydrogen peroxide water bath at 100°C for 4 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified flax fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 10:1 and heated at 100°C for 2 hours, and then the flax fiber in a mass ratio of 1:10 and the above mixed solution were allowed to stand at 70°C for 48 hours. After that, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 86%. The tensile strength of the hydrogel was 2.1MPa and the tensile strain was 65%.

[0040] Example 3

[0041] Jute was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 15 hours to partially remove lignin and hemicellulose; then washed with clean water. The jute fiber with partially removed lignin was placed in 30wt.% hydrogen peroxide in a water bath at 100°C for 6 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified jute fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 10:1 and heated at 100°C for 2 hours, and then the hemp fiber in a mass ratio of 1:10 and the above mixed solution were allowed to stand at 70°C for 48 hours. After that, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 93%. The tensile strength of the hydrogel was 1.9MPa and the tensile strain was 68%.

[0042] Example 4

[0043] The hemp fiber was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 15 hours to partially remove lignin and hemicellulose; then washed with clean water. The hemp fiber with partially removed lignin was placed in 30wt.% hydrogen peroxide in a water bath at 100°C for 5 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified hemp fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 10:1 and heated at 100°C for 2 hours, and then the hemp fiber in a mass ratio of 1:10 and the above mixed solution were allowed to stand at 70°C for 48 hours. After that, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 83%. The tensile strength of the hydrogel was 1.9MPa and the tensile strain was 67%.

[0044] Example 5

[0045] Ramie was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 5 hours to partially remove lignin and hemicellulose; then washed with clean water. The partially lignin-removed ramie fiber was then placed in a 5wt.% hydrogen peroxide water bath at 100°C for 4 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified ramie fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 9:1 and heated at 100°C for 0.5 hours, and then the swollen ramie fiber and the above mixed solution were placed at 70°C for 24 hours in a mass ratio of 1:8. Finally, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 80%. The tensile strength of the hydrogel is 2.3MPa and the tensile strain is 62%.

[0046] Example 6

[0047] Ramie was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 10 hours to partially remove lignin and hemicellulose; then washed with clean water. The partially lignin-removed ramie fiber was then placed in a 10wt.% hydrogen peroxide water bath for 6 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified ramie fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 12:1 and heated at 100°C for 1 hour, and then the swollen ramie fiber and the above mixed solution were placed at 70°C for 48 hours in a mass ratio of 1:12. Finally, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 86%. The tensile strength of the hydrogel is 2.1MPa and the tensile strain is 65%.

[0048] Example 7

[0049] Ramie was placed in a mixed solution of sodium hydroxide, sodium sulfite and water in a mass ratio of 4:1:16, and treated in a water bath at 100°C for 15 hours to partially remove lignin and hemicellulose; then washed with clean water. The partially lignin-removed ramie fiber was then placed in a 30wt.% hydrogen peroxide water bath at 100°C for 6 hours to further remove lignin; then washed with clean water, frozen at -12°C for 2 hours, and quickly taken out and dried in a freeze dryer for 24 hours. After that, the dried delignified ramie fiber was placed in a mixed solution of N,N-dimethylacetamide and lithium chloride in a mass ratio of 13:1 and heated at 100°C for 2 hours, and then the swollen ramie fiber and the above mixed solution were placed at 80°C for 72 hours in a mass ratio of 1:15. Finally, the obtained sample was placed in clean water to displace the chemical residues to obtain a high-strength pure cellulose hydrogel with a water content of 92%. The tensile strength of the hydrogel is 1.8MPa and the tensile strain is 69%.

Claims

1. A method for preparing a high-strength pure cellulose hydrogel, characterized in that: The method comprises the following steps: The hemp plant is placed in a mixed aqueous solution of sodium hydroxide and sodium sulfite and heated in a water bath to partially remove lignin and hemicellulose; then washed with clean water to remove residual chemicals; The hemp fiber obtained in step (1) is placed in a hydrogen peroxide water bath for heating to further remove lignin; then washed with clean water and freeze-dried; The dried hemp fiber is placed in a mixed solution of N, N-dimethylacetamide and lithium chloride for heating, so that the hemp fiber is swollen, the mass ratio of the swollen hemp fiber to the mixed solution is in the range of 1:8 to 1:15, and then the swollen hemp fiber and the mixed solution are allowed to stand at a temperature of 70-80° C. for 12-72 hours; wherein the mass ratio of the mixed solution of N, N-dimethylacetamide and lithium chloride is in the range of 9:1 to 13:1, the heating treatment temperature is 100° C., and the heating treatment time is 0.5-2 hours; The material after static treatment is replaced with clean water to obtain a mixed solution to obtain a high-strength pure cellulose hydrogel; the micron-sized hemp fibers in the hydrogel are arranged longitudinally to form a reinforcing skeleton, and the partially dissolved regenerated nanofibers are dispersed around the micron-sized hemp fibers to form a three-dimensional cross-linked network structure; the diameter of the micron-sized hemp fibers is 15-50 μm, and the diameter of the regenerated nanofibers is 5-60 nm.

2. The method for preparing a high-strength pure cellulose hydrogel according to claim 1, characterized in that: In step (1), the water bath heating temperature is 100° C. and the treatment time is 5-15 hours.

3. The method for preparing a high-strength pure cellulose hydrogel according to claim 1, characterized in that: In step (2), the concentration of the hydrogen peroxide solution is 5-30 wt.%, the water bath temperature is 100° C., and the heating time is 1-6 hours.

4. The method for preparing a high-strength pure cellulose hydrogel according to claim 1, characterized in that: The hydrogel has a water content of 80-93%, a longitudinal tensile strength range of 1.8-2.6 MPa, and a tensile strain of 50-69%.

Citation Information

Patent Citations

  • Structure-controllable pure cellulose aerogel and preparation method thereof

    CN109762205A

  • Plant fiber with ultrahigh mechanical properties and preparation method thereof

    CN112227063A